The $PID_{n}^{m}$ Controller Tuning for Temperature and % RH Control in a Chamber Using Simulink Desktop Real-Time - Nuengsatree Boonseng; Arjin Numsomran; V. Tipsuwanporn; Jutarut Chaoraingern (My University, 2023)
This paper presents the development and implementation of a $PID_{n}^{m}$ controller tuning technique for temperature and relative humidity (% RH) control in a chamber using Simulink Desktop Real-Time. The proposed controller tuning method aims to achieve precise and robust control of temperature and % RH in environments where accurate environmental conditions are critical, such as laboratories, manufacturing facilities, and storage units. The $PID_{n}^{m}$ controller incorporates additional derivative, integral, and filter terms to enhance control performance. The design process involves analyzing the system dynamics, modeling the chamber's temperature and % RH response, and selecting appropriate control parameters. The tuning strategy takes into account the specific requirements of temperature and % RH control, such as fast response, a lower percent of overshoot, and steady-state accuracy. Simulink Desktop Real-Time is utilized for the real-time implementation of the control algorithm, providing a reliable and efficient platform for testing and validation. Experimental results demonstrate the effectiveness of the proposed methodology in achieving precise and stable temperature and % RH control.
Keywords: Advanced Control Systems Design; Advanced Control Systems Optimization; Experimental Learning in Engineering